1975
DOI: 10.1016/0040-1951(75)90095-5
|View full text |Cite
|
Sign up to set email alerts
|

The paleomagnetism of the Speckled Sandstones of Early Permian Age from the Salt Range, Pakistan

Abstract: Paleomagnetic results are presented from the Speckled Sandstones, of probably Early Permian age, from the Salt Range in Pakistan. The analysis includes 86 specimens from nine sites collected at three individual localities. All specimens were subjected to progressive, thermal treatment which revealed the characteristic directions of magnetization, with a mean value,of D = 92.2O, Z = +46.7', ags = 13ON, 137.5OE, with 6, = 5.1° and 6, = 7.3'. The paleomagnetic pole is located at 9.5'. This position agrees well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The four Early Permian lithostratigraphic units of the Salt Range developed during four stages: the Asselian, Sakmarian, Artinskian and Kungurian (Pascoe 1959;Wensink 1975;Veevers and Tewari 1995). These units are now known to be each bounded by diachronous surfaces (Ghazi 2009), the nature of the diachronous relationships being demonstrable by the occurrence of distinctive biostratigraphic and lithostratigraphic characteristics (figure 4).…”
Section: Lithostratigraphic Analysis Of the Early Permian Succession mentioning
confidence: 99%
“…The four Early Permian lithostratigraphic units of the Salt Range developed during four stages: the Asselian, Sakmarian, Artinskian and Kungurian (Pascoe 1959;Wensink 1975;Veevers and Tewari 1995). These units are now known to be each bounded by diachronous surfaces (Ghazi 2009), the nature of the diachronous relationships being demonstrable by the occurrence of distinctive biostratigraphic and lithostratigraphic characteristics (figure 4).…”
Section: Lithostratigraphic Analysis Of the Early Permian Succession mentioning
confidence: 99%
“…21 and 22) from the Salt Range and those from the Peninsular Shield may be fortuitous and that the palaeomagnetic poles for the Purple Sandstone and the Salt Pseudomorph beds from the Salt Range may be rotated anticlockwise through 7 5 O around a rotation pole located at 33' N, 74' E. According to Crawford, the Salt Range was aligned along the main strike of the Himalayas, but was rotated to occupy the present position as a consequence of tectonic movement taking place some time in the Late Tertiary. However, Wensink (1975) and Klootwijk (1976) have pointed out that the position for Permo-Carboniferous Speckled Sandstone from the Salt Range is located close to those for contemporaneous formations from the Peninsular Shield, although they did not apply the rotation correction suggested by Crawford for the Salt Range palaeomagnetic data. In this paper, we have shown that the Durgapipal volcanics, located in a folded chain (the Lesser Himalayas), also show an agreement with the Permian results from the Salt Range and the Peninsular Shield, without invoking any block rotation.…”
mentioning
confidence: 94%
“…While formations belonging to the Mesozoic era have been studied extensively, only scanty data are available for the Tertiary period, the Palaeozoic era and for some Pre-Cambrian horizons. The data have been summarized and reviewed periodically (Athavale et al 1970;McElhinny 1973;Wensink 1973Wensink , 1975Klootwijk 1976 etc.). The palaeomagnetic polar wandering path based on the Indian data so far available shows a large gap between the Late Pre-Cambrian-Cambrian and Upper Carboniferous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation